A Summary of the survey report of Hydrological Systems in the Great Virunga Landscape (Uganda, Rwanda and DRC) - Institute of Tropical Forest Conservation (Institute of tropical forest conservation, 2015)
Communities in the GVL face water shortages inspite of living adjacent major catchment areas. The water sources are unevenly distributed and few. Still much fewer water sources flow permanently. This makes the local community members to travel long distances and risk to collect water from the protected areas and other unprotected water sources within the landscape. Water demand far outstrips the supply so that where protected water sources have been installed there are marked with long queues and/or rationing of water. Each household uses between 20 – 60 litres of water per day. This is far below the required standard of 15 litres per person per day. Some domestic chores like keeping good hygiene are foregone because of lack of enough water in the households. Water from unprotected sources is often of poor quality making it a hazard to local community livelihoods. The water from all unprotected water sources was found to be contaminated with feacal material making it unfit for human consumption. Water sources are also adversely affected by high rates of erosion within the protected areas due to the steep slopes and outside the protected areas due to poor agricultural practices. Several action points are recommended, key being the protection of the current sources, expansion of rain harvesting technologies, and improvement in community sanitation to make the water safe. Soil and water conservation methods should be implemented in areas under agriculture to avoid siltation and pollution of water sources like wetlands and rivers.